SENATE BILL 2070 CRITICAL ISSUES (Tufts Archival Research Center, 2007)
Summary of the Critical Issues of Senate Bill 2070 which would require California to adopt a cigarette fire safety standard and would ban the sale of cigarettes not meeting this requirement. Lists points of opposition to the bill. Asks whether or not the harm from the bill would be greater than the benefit from it. Claims that California already has fire safety standards which are effective.